Efektifitas Latihan Terarah Penderita Post Sindrom Koroner Akut Upaya Memperbaiki Otot Jantung di RS Siti Khodijah Sepanjang - Badriyah, Fatin Lailatul (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2017)
Cardiovascular disease and very scary is acute coronary syndrome (ACS). It is currently one of the leading causes of death indeveloped and developing countries, including Indonesia. SKA can be either acute my of cardial infarction, including ST-segment elevation MI (STEMI) and non-segment elevation MI (NSTEMI), and unstable angina. Globally become the first cause of death in developing countries, replace mortality due to infection. Systematic effort is needed and intensively to prevent the increasing cases of illness, among others with cardiac rehabilitation. One of cardiac rehabilitation can be done is directed physical exercise. To determine the effect of exercise derected on the function of cardiac muscle, as sessed based on the results of blood pressure, pulse and ECG. Methods the study used a quasi-experiment design, there search subjects to taling 64 people divided into intervention groupas 32 peoples and control group of 32 peoples, carried out in hospital cardiac clinic Siti Khodijah Surabaya. The Results Wilcoxon test and Mann Whitney test, obtained results there is a significant influence on tension with p-valueof 0.001(p <0.05), there is not significant effect on the change of the pulse with the p-value of 1.000>(p <0.05), and significantly influence changes in EKG with P-value 0.000 <(P <0.05). The results of the Nagelkerke test and Chi-square, obtained results physical exercise directed has contributed to the tension of 16.4%, OR=9.552, while the ECG changes of 47.0%, OR=27.617. Exercise directed has a significant effect on blood pressure and EKG, where the directional physical exercise has a more significant effecton blood pressure than the ECG.Â Keyword : Exercise Directed And Coronary Acute Syndrome (ACS)